HUBUNGAN PENERIMAAN DIRI DENGAN KUALITAS HIDUP PASIEN KANKER PAYUDARA DI RSUP. PROF DR. R.D KANDOU - Ferlan Ansye Pondaag; Adriani Natalia M; Sembiring, Erika Emnina (Jurnal Keperawatan Widya Gantari Indonesia, 2023)
Breast cancer and its treatment cause serious psychological problems in patients, such as low self-esteem and feelings of pride, anxiety, even depression and not being ready to accept the condition of the disease they are currently experiencing. Breast cancer patients with low self-acceptance tend to experience feelings of depression, body image disturbances and decreased quality of life. Quality of life can be an important parameter in assessing how well a person functions after being diagnosed and undergoing treatment therapy. The purpose of this study was to examine the correlation of self-acceptance with the quality of life of breast cancer patients. This research is a descriptive research with cross sectional method. Consecutive sampling is a sampling technique in this study with a total sample of 74 breast cancer patients treated at Prof. Dr. R.D Kandou Hospitals. The measuring tools used are the Acceptance of Illness Scale questionnaire to assess patient self-acceptance and the EORTC QLQ C-30 to assess patient quality of life. Univariate data analysis in the form of descriptive statistics and bivariate data analysis using the Spearman test. The research results showed that more than half, namely 51.4% of breast cancer patients had moderate self-acceptance and almost all, namely 91.9% of breast cancer patients, had moderate quality of life. Based on the Spearman statistical test, it shows that self-acceptance is correlated with the quality of life of breast cancer patients (p < 0.05). Better self-acceptance also improves the quality of life of breast cancer patients. Self-acceptance and quality of life for breast cancer patients need to be improved. This aims to make patients enthusiastic about undergoing therapy programs and have high motivation to recover.